Lung Cancer Screening - Gutierrez, Antonio; Suh, Robert; Abtin, Fereidoun; Genshaft, Scott; Brown, Kathleen (Seminars in Interventional Radiology, 2013)
Lung cancer is the leading cause of cancer death. Although smoking prevention and cessation programs have decreased lung cancer mortality, there remains a large at-risk population. Dismal long-term survival rates persist despite improvements in diagnosis, staging, and treatment. Early efforts to identify an effective screening test have been unsuccessful. Recent advances in multidetector computed tomography have allowed screening studies using low-dose computed tomography (LDCT) to be performed. This set the stage for the National Lung Screening Trial that found that annual LDCT screening benefits individuals at high risk for lung cancer. An understanding of the harmful effects of lung cancer screening is required to help maximize the benefits and decrease the risks of a lung cancer screening program. Although many questions remain regarding LDCT screening, a comprehensive lung cancer screening program of high-risk individuals will increase detection of preclinical and potentially curable disease, creating a new model of lung cancer surveillance and management.
Keywords: lung cancer; screening; clinical trials; low dose computed tomography; chest radiography; pulmonary nodules; lung cancer screening program